The Effect of Moderate-Intensity Physical Exercise on Interleukin-6 Level and Lymphocyte Count in Leprosy Reaction Patient - Roy, Adryan; Nasihun, Taufiqurrachman; Sumarawati, Titiek (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Introduction: Leprosy reaction is an immunity declining reaction marked with inflammation which may cause permanent disability. Physical exercise may improve body’s immune system. Objective: To prove the effect of moderate-intensity physical exercise on the interleukin-6 level and lymphocyte count in leprosy reaction patient.Methods: The quasi-experimental research with pretest and posttest and a control group design used 30 respondents consisting of 14 interventions and 16 controls. The intervention group was given moderate-intensity physical exercise 60%-79% in the form of static cycle at a frequency of 4 times weekly, 150 minutes per week. Corticosteroid was always administered to the two groups as a standard therapy. The interleukin-6 level was measured using ELISA method and lymphocyte count was measured using hematology analyzer.Result: The Mann-Whitney analysis shows that the mean difference in IL-6 level between pretest and posttest with the intervention group (-7.1429±25.2369) is significantly lower than that of the control group (8.8125±11.2025), p<0.05. On the contrary, the Independent t-test analysis shows that the mean difference in lymphocyte count between pretest and posttest with the intervention group (0.7407±0.41236) is significantly higher than that of the control group (-0.4500±0.42415), p<0.05. Conclusion: Physical exercise at moderate intensity in the form of aerobics using static cycle at a frequency of 4 times weekly, with duration of 150 minutes per week decreases interleukin-6 level and increases lymphocyte count in leprosy reaction patient.